Quantitative determination of adsorption activity of adsorbents obtained on the basis of cotton stalk and cotton boll - Kuchkarova, Durdona; Soliye, Mahammadjon; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article discusses adsorbents used to reduce water and air pollution, which is one of the current problems of our time. The importance of adsorbents today has been studied. Methods of their production and sources of raw materials have been considered. Information is provided on the need to pay attention to the sufficiency of their sources, low cost, environmental safety, recyclability, and carbon content when choosing raw materials for obtaining adsorbents. Also, the raw material base of cotton stalks and cotton bolls selected for obtaining adsorbents in the republic has been studied. Methods for obtaining adsorbents by thermochemical activation based on cotton stalks and cotton bolls and determining the sorption activity of the obtained adsorbents are presented. The iodine number of adsorbents was used to determine the sorption properties of the obtained activated carbons. The iodine number of adsorbents obtained by thermochemical activation with solutions of NaOH and KOH of different concentrations was determined according to State Standard 33618-2015. Among them, adsorbents activated with 30% NaOH and KOH solutions showed good results in terms of sorption properties and economy. Based on these results, adsorbents with good results in terms of iodine number were selected for further analysis.